2007
DOI: 10.1088/0953-8984/19/3/036213
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of pressure effects on the magnetic and the magnetocaloric properties of the intermetallic compounds DyCo2and Er(Co1−xSix)2

Abstract: The effect of external pressure on the magnetic properties and magnetocaloric effect of R(Co 1-x Si x ) 2 [R= Er, Dy and x=0, 0.025 and 0.05] compounds has been studied. The ordering temperatures of both the parent as well as the Si substituted compounds are found to decrease with pressure. In all the compounds, the critical field for metamagnetic transition increases with pressure. It is seen that the magnetocaloric effect in the parent compounds is almost insensitive to pressure, while there is considerable … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Compounds showing field-induced magnetic transitions and/or structural transitions have been found to exhibit very large MCE, as in the case of Gd 5 Si 2 Ge 2 . [9][10][11] Giant magnetocaloric effect was also found in LaFe 11.4 Si 1.6 , 12 MnAs, 13,14 FePMnAs, 15 RCo 2 , 16,17 Heusler alloys, 18 manganites, 19 etc. In most of these cases, the giant MCE is a result of a first-order ferromagnetic ͑FM͒ to paramagnetic transition.…”
Section: Introductionmentioning
confidence: 80%
“…Compounds showing field-induced magnetic transitions and/or structural transitions have been found to exhibit very large MCE, as in the case of Gd 5 Si 2 Ge 2 . [9][10][11] Giant magnetocaloric effect was also found in LaFe 11.4 Si 1.6 , 12 MnAs, 13,14 FePMnAs, 15 RCo 2 , 16,17 Heusler alloys, 18 manganites, 19 etc. In most of these cases, the giant MCE is a result of a first-order ferromagnetic ͑FM͒ to paramagnetic transition.…”
Section: Introductionmentioning
confidence: 80%
“…It has been experimentally shown that the magnetocaloric potentials ∆S iso and ∆T ad in ErCo 2 , HoCo 2 and DyCo 2 exhibit a jump around the magnetic ordering temperature, due to the first order magnetic phase transition [250][251][252][253][254][255][256][257][258][259][260][261][262][263]. In the other compounds of the RCo 2 series the phase transition is of second order and the magnetocaloric potentials exhibit the usual behavior.…”
Section: Magnetocaloric Effect In Rco 2 Compoundsmentioning
confidence: 99%
“…6 Moreover, the study of the pressure effects on DyCo2 reveals that the Curie temperature decreases with the application of external pressure due to the contraction of the lattice parameter. 22 Doping by interstitial elements (H, C, and B) usually leads to an increase of the lattice constant, and the H absorption has been successfully applied to adjust the Curie temperature of La(Fe0.89Si0.11)13 from 190 K to room-temperature, while preserving the first-order of the magnetic transition. 15 However, the hydrogenation treatment for DyCo2 leads to disproportionation and amorphization of the compound.…”
Section: і Introductionmentioning
confidence: 99%